KECENDERUNGAN POPULASI Rafflesia zollingeriana Kds. DI TAMAN NASIONAL MERU BETIRI, JAWA TIMUR (Population Trend of Rafflesia zollingeriana Kds. in Meru Betiri National Park, East Java) - Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Rafflesia zollingeriana Kds. is icon for the conservation of flora in Meru Betiri National Park. Population of R. zollingeriana in the last fifteen years tend to decrease. This condition due to natural disaster and illegal utilization of the flower.Key words : Rafflesia zollingeriana, conservation, flora, Meru Betiri National Park